Exploring the shift from online English learning to in-person instruction after COVID-19: a classroom action research study - Gufron, Gufron; Md Zamin, Ainul Azmin (ARJHSS, 2023)
This study, "Examining the Transition from Learning English Online to Offline Instruction: A Classroom Action Research", investigates the effectiveness of transitioning from online English learning to offline instruction in a university English language centre. The study adopts a mixed methods approach, utilizing interviews, observations, and questionnaires to gather comprehensive data. The study aims to explore the challenges and benefits of transitioning from online to offline instruction and assess the impact of this transition on students' language acquisition and overall learning experience. The study begins with qualitative interviews with students to gain insights into their perceptions and experiences regarding the shift from online to offline instruction. Subsequently, classroom observations are conducted to assess the effectiveness of the teaching strategies employed during offline instruction. The observations provide valuable information on student engagement, participation, and progress in a face-to-face learning environment. A quantitative approach is used by distributing questionnaires to complement the qualitative findings. The questionnaires gather data on online learning experience, transition experience, and offline instruction experience. The study found students' preference for offline classes due to better interaction, comfort, comprehension, and language practice. Offline learning leads to higher satisfaction, improved language skills, and fosters engagement, while online learning may have limitations.